The effect of microbial calcite precipitation on the retention properties of unsaturated fine-grained soils: discussion of the governing factors - Saffari R.; Nikooee E.; Habibagahi G. (E3S Web of Conferences, 2020)
In recent years, biogeotechnology has been introduced as a novel and environmentally friendly technique for soil improvement. The need to address global warming and the adverse environmental effects of the chemical additives have led to the emergence and development of the techniques which use calcite producing microorganisms in order to improve soil mechanical properties. While the effects of microbial induced calcite precipitation (MICP) on the hydraulics and mechanics of saturated coarse-grained soils have been well examined and studied, there is not yet much information on the effects these microorganisms would have on the unsaturated soil mechanical behaviour. The first step, in this regard, is to understand the effect of the processes involved in the MICP on the soil retention properties. Soil water suction is a key factor controlling soil hydraulic and mechanical behaviour. In this study, the influence of MICP on the soil total suction in an unsaturated fine-grained soil sample has been explored using filter paper experiment. The results of this study revealed that by increasing the amount of bacterial solution, the soil saturation-total suction curves are significantly affected. The soil water retention changes are attributed to the change in double layer thickness as well as the precipitation of calcite crystals.